Pengaruh Edukasi Melalui Media Video Triage START Terhadap Pengetahuan, Sikap, dan Keterampilan Mahasiswa Sarjana Keperawatan - I Kade Wira Darma; Ni Luh Putu Inca Buntari Agustini; Yustina Ni Putu Yusniawati; Ni Made Dewi Wahyunadi; I Wayan Edi Sanjana (Poltekkes Kemenkes Kupang, 2026)
Background: The Simple Triage and Rapid Treatment (START) system is a key method for determining the priority of disaster victim management based on their respiratory status, circulation, and level of consciousness. It is important for nursing students to master this system in order to be prepared for emergency situations. However, conventional learning methods are often less effective, making more engaging approaches necessary. Objectives: This study aimed to evaluate the effectiveness of video-based education in improving students’ knowledge, attitudes, and skills regarding START triage. Methods: This study employed a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 128 fourth-year nursing students at ITEKES Bali. The intervention provided was an educational video on START triage. The study was conducted from September 22 to September 27, 2025. Data were collected using questionnaires and analyzed with the Wilcoxon test. Results: A significant increase in knowledge was found after the intervention, with all participants (128 students, 100%) demonstrating good levels of knowledge. Positive changes in attitudes were also observed among all participants (128 students, 100%), along with improved skills, where the majority showed good performance (119 students, 93.0%). Conclusions: Educational intervention through START triage video media was proven to improve the knowledge, attitudes, and skills of nursing students. This video-based learning media has the potential to become an innovative teaching method in disaster preparedness and emergency training.